Revision of the western Palaearctic species of Aleiodes Wesmael (Hymenoptera, Braconidae, Rogadinae). Part 2: Revision of the A. apicalis group - Cornelis van Achterberg (ZooKeys, 2020)
The large parasitoid wasp genus Aleiodes Wesmael, 1838, (Hymenoptera: Braconidae: Rogadinae) has a world-wide distribution and in the western Palaearctic region it forms a moderately prominent element of the braconid fauna. Despite the relatively large size and/or abundance of several species, and the frequency with which they are reared by lepidopterists, there are no reliable identification keys to the western Palaearctic species before the first part of this series was published. Both first authors assembled specimens from many collections and all available biological data for this revision during 40 years. The second author has reared many western European species of Aleiodes from their Lepidoptera hosts, and also received donations of specimens reared by a large number of lepidopterists. The third author analysed the molecular data assembled by him and the second author. Investigation of Aleiodes host ranges has also involved some experimentation using short-term cultures by the second author, and in some cases this has been motivated by, and crucial for, elucidating species-level taxonomy. In this second paper we give an illustrated key to the Aleiodes apicalis species group what are in general the larger and more conspicuous species. The biology, host associations and phenology are discussed for the keyed species and, in total, six new species are described and fourteen new synonyms are proposed.